Assessment Methods of Sport-Induced Neuromuscular Fatigue: A Scoping Review - Jose L. Muñoz-Gracia; Eduard Alentorn-Geli; Martí Casals; Timothy E. Hewett; Ernest Baiget (International Journal of Sports Physical Therapy)
# Background Neuromuscular fatigue (NMF) has been defined as the exercise-induced performance decrease associated with muscular activity. # Purpose The primary aim was to identify the available evidence regarding the testing tasks used to assess NMF in the lower limbs and to determine the most commonly used test in specific sports. The secondary aim was to group the tests found according to the type of sport. # Study Design Scoping review. # Methods A literature search was conducted in PubMed, ScienceDirect, SportDiscus, and Web of Science databases. Search terms were “neuromuscular fatigue” and ("test" or "tests" or "testing task" or "task"). Studies that analyzed healthy humans, voluntary contractions, and participants under 50 years old were included. Studies in which the main focus was not NMF, the lower limbs were not analyzed, the knee joint was not involved, the pre-post analysis of fatigue was not used, or there was no sport fatigue protocol between tests were excluded. The PRISMA-ScR guidelines were followed. # Results A total of 97 studies were included. Most of these included males (68.0%) and professional athletes in their samples (46.4%) . The data most commonly studied for NMF were athletes from team sports (74.2%), specifically soccer (32.0%) and rugby (18.6%). Matches and trainings sessions were the fatiguing protocols (59.8%), whereas vertical jumps (82.5%), measured by force platforms (77.5%), was the test most commonly used. The most commonly evaluated parameters were jump height (75.0%) and peak power (41.3%). Tests varied different according to the sport, and vertical jumps (77.8%), and sprints (15.3%) were the tests most commonly used for the athletes in team sports. For athletes in individual sports, vertical jumps (72.0%) and isometric knee extension/knee flexion (24.0%) were most utilized. # Conclusions Different fatigue protocols, test tasks, materials, and variables are used to assess NMF. Veritcal jump is the most commonly utilized test task for athletes of both team and individual sports. It appears necessary to choose the most appropriate test tasks according to each type of sport.